PENINGKATAN HASIL BELAJAR SISWA MATA PELAJARAN SEJARAH MELALUI MATODE SOKRATIS PADA SISWA KELAS XI IPS MAN LUWU - Nahar Bana (STKIP Pembangunan Indonesia Makassar, 2022)
This research is classroom action research with qualitative data exposure inthe from of cumulative frequency data, the subject of research is a student of class XII IPS MAN Luwu Kab. Luwu, data collection with observation and testing techniques. The data analysis technique used is the statistical analysis of cumulative frequency distribution. The results of this study show that learning with socrates can improve the Learning Results of Student of History Class XII IPS MAN Luwu Kab. Luwu with an overall average of 79 or equivalent to the outcome of learning above the level of skill. In connection with this, the researchers suggested that other class teachers, in partikuler class teacher XII IPS MAN Luwu Kab. Luwu, can apply Socrates learning in presenting learning materials in order to optimisze the ability of students in solving issues of historical subjectsKeyword : students’ achievement; power point; moral praised